Two-year outcome of an eye that underwent hyperopic LASIK following inadvertent myopic SMILE lenticule in situ implantation - Jing Zhao; Jianmin Shang; Lingling Niu; Haipeng Xu; Dong Yang; Yu Zhao; Dan Fu; Xingtao Zhou (BMC Ophthalmology, 2019)
Abstract Background This report describes a case in which hyperopic femtosecond laser-assisted in situ keratomileusis (FS-LASIK) was performed following small incision lenticule extraction (SMILE) lenticule in situ implantation. Case presentation The hyperopic left eye of a 46-year-old patient with refraction of + 7.75 diopters sphere (DS)/− 1.25 diopters cylinder (DC) × 5° and corrected distance visual acuity (CDVA) of 20/50 mistakenly underwent the SMILE procedure for myopic astigmatism (− 8.50 DS/− 1.50 DC × 175°) due to medical negligence. The extracted lenticule was subsequently re-implanted in situ. After 8 months, the left eye underwent FS-LASIK to correct hyperopia and astigmatism (+ 5.0 DS/− 0.75 DC × 100°). Two years after FS-LASIK, corneal tomography showed no ectasia and microscopy revealed transparent cornea. The left eye exhibited CDVA of 20/50 with refraction of − 0.75 DS/− 0.25 DC × 165°. Conclusions SMILE lenticule in situ implantation offers a solution for corneal volume and thickness restoration. FS-LASIK provides feasible correction of refractive error following lenticule re-implantation. Future studies are needed for determining the effectiveness of the treatment.